Development of local-based biology teaching modules: Conservation of Tapanuli orangutans (Pongo tapanuliensis) in the Batang Toru area as support for biodiversity material - Linawati Linawati; Panut Hadisiswoyo; Syarifah Widya Ulfa; Zulfiana Herni (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2025)
In the 21st century, innovation is needed in the development of learning media that is not only academically valid, but also easy to use by teachers and students and effective in increasing understanding of biodiversity and conservation. Tapanuli Orangutan conservation is a field survey activity to find out about the protection of orangutans in their natural habitat. This study aimed to develop a Biology module based on the conservation of the Tapanuli Orangutan (Pongo tapanuliensis) in the Batang Toru area as a support for valid, practical, and effective Biodiversity material. The module was developed with the 4D development model by Thiagarajan (Define, Design, Develop & Disseminate) The instruments used in the study were in the form of a questionnaire sheet analyzing the needs of Biology teachers and students, material expert validation sheet, media expert validation sheet, Biology teacher response questionnaire and students to measure the ability to use presest and posttest. The validation results show that the module is included in the valid criteria with validity in media experts 78.75% and material experts 92.30% so it is feasible to use in Biology learning. The results of the response questionnaire showed that the module was included in the very practical criteria with practicality in the Biology teacher's response of 100% and the students' response of 96%. The module is included in the effective criteria with an N-gain achievement of 0.81. Based on these results it can be concluded that the module that has been developed is declared feasible to use in learning Biology. So that the resulting module can be an innovative teaching material for teachers and can be used in the learning process and future research.Abstrak: Pada abad 21 ini diperlukan inovasi dalam pengembangan media pembelajaran yang tidak hanya valid secara akademik, tetapi juga mudah digunakan oleh guru dan siswa serta efektif dalam meningkatkan pemahaman terhadap biodiversitas dan konservasi. Konservasi Orangutan Tapanuli merupakan kegiatan survei lapangan guna mengetahui tentang perlindungan Orangutan di habitat aslinya. Penelitian ini ditujukan untuk mengembangkan modul Biologi berbasis konservasi Orangutan Tapanuli (Pongo tapanuliensis) yang ada di daerah Batang Toru sebagai penunjang materi Biodiversitas yang valid, praktis, dan efektif. Modul dikembangkan dengan model pengembangan 4D oleh Thiagarajan (Define, Design, Develov & Disseminate) Instrumen yang digunakan pada penelitian adalah berupa lembar angket analisis kebutuhan guru Biologi dan peserta didik, Iembar validasi ahli materi, lembar validasi ahli media, angket respon guru Biologi dan peserta didik untuk mengukur kemampuan menggunakan presest dan posttest. Hasil validasi menunjukkan bahwa modul termasuk dalam kriteria valid dengen kevalidan pada ahli media 78,75% dan ahli materi sebesar 92,30% sehingga layak digunakan dalam pembelajaran Biologi. Hasil angket respon menunjukkan bahwa modul termasuk dalam kriteria sangat praktis dengan kepraktisan pada respon guru Biologi sebesar 100% dan respon peserta didik sebesar 96%. Modul termasuk dalam kriteria efektif dengan capaian N-gain sebesar 0,81. Berdasarkan hasil tersebut dapat disimpulkan bahwa modul yang telah dikembangkan dinyatakan layak digunakan dalam pembelajaran Biologi. Sehingga modul yang dihasilkan dapat menjadi bahan ajar yang inovatif bagi guru serta dapat digunakan dalam proses pembelajaran dan penelitian kedepannya.